Electrosorption of copper ions by poly(m-phenylenediamine)/reduced graphene oxide synthesized via a one-step in situ redox strategy. (1st June 2015) - Li, Kaijian; Guo, Dengfeng; Lin, Furong; Wei, Yong; Liu, Wenjie; Kong, Yong
Graphical abstract: Due to the excellent electrical conductivity and mechanical properties of RGO, the electrosorption of Cu 2+ based on the P m PD/RGO is superior to that on the P m PD and RGO reduced from hydrazine. Highlights: P m PD/RGO is synthesized via a one-step in situ redox strategy. For the first time, P m PD/RGO is used as electrode material for Cu 2+ electrosorption. Regeneration of the P m PD/RGO electrode is easily achieved by electrodesorption. The P m PD/RGO can undergo 31 successive electrosorption/electrodesorption cycles. Abstract: We present an efficient Cu 2+ electrosorption based on poly( m -phenylenediamine)/ reduced graphene oxide (P m PD/RGO), which is formed via simultaneous reduction of graphene oxide (GO) to RGO and polymerization of m -phenylenediamine ( m PD) to P m PD. The as-prepared P m PD/RGO composites were characterized by transmission electron microscopy (TEM), Fourier transform infrared (FT-IR) spectroscopy, thermo gravimetric analysis (TGA), and X-ray photoelectron spectroscopy (XPS). The electrosorption behaviors of Cu 2+ on the P m PD/RGO electrode were investigated in detail, and the results demonstrated that the P m PD/RGO electrode exhibited a favorable performance for the removal of Cu 2+ . Due to the excellent electrical conductivity and mechanical properties of RGO, the electrosorption of Cu 2+ based on the P m PD/RGO is superior to that on the P m PD.